Use of the CRISPR/Cas9 System for Genome Editing of Immune System Cells, Defense Against HIV-1 and Cancer Therapies - Assis, Amanda Freire; Hernandez, Cesar Speck; Cotrim-Sousa, Larissa; Felicio, Rafaela Martins; Oliveira, Ernna Hérida; Teixeira, Lorena Alves; Valente, Valeria [UNESP]; Silva, Wilson Araújo; Passos, Geraldo A. (Cambridge University Press (CUP), 2018)
A summary is not available for this content so a preview has been provided. Please use the Get access link above for information on how to access this content.